2016
DOI: 10.1245/s10434-016-5240-1
|View full text |Cite
|
Sign up to set email alerts
|

TARGIT-R (Retrospective): North American Experience with Intraoperative Radiation Using Low-Kilovoltage X-Rays for Breast Cancer

Abstract: IORT use for the treatment of breast cancer is significantly increasing in North America, and physicians are selecting low-risk patients for this treatment option. Low complication and local recurrence rates support IORT as a treatment option for selected women with early stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
3
24
0
6
Order By: Relevance
“…For example, the fact that the largest applicators (4.5 and 5 cm) were utilized in 87% of patients indicates that the surgical resection specimens were unusually large despite the predominance of tumors under 2 cm. In contrast, the average applicator diameter used in the TARGIT‐A trial was 3.5‐4 cm even with a mean tumor size that was similar to that reported by Zur et al Similarly, the 3.5 and 4.0 cm applicators were used in 58% of patients in the TARGIT Retrospective Registry, a U.S. retrospective registry of 935 TARGIT recipients . In addition, in a personal series of 100 recent TARGIT cases, the mean applicator diameter was 3.78 cm.…”
supporting
confidence: 60%
“…For example, the fact that the largest applicators (4.5 and 5 cm) were utilized in 87% of patients indicates that the surgical resection specimens were unusually large despite the predominance of tumors under 2 cm. In contrast, the average applicator diameter used in the TARGIT‐A trial was 3.5‐4 cm even with a mean tumor size that was similar to that reported by Zur et al Similarly, the 3.5 and 4.0 cm applicators were used in 58% of patients in the TARGIT Retrospective Registry, a U.S. retrospective registry of 935 TARGIT recipients . In addition, in a personal series of 100 recent TARGIT cases, the mean applicator diameter was 3.78 cm.…”
supporting
confidence: 60%
“…The 2% rate of local recurrence is similar to the TARGIT‐A trial, which demonstrated a 3.3% rate of local recurrence with 29 month follow‐up, though this trial included higher risk patients . Similarly, TARGIT‐R, a multi‐institutional retrospective registry, identified a local recurrence rate of 2.3% with 23‐month follow‐up . Similar results have been observed in other institutional series evaluating IORT; Chowdhry et al evaluated 110 patients receiving IORT.…”
Section: Discussionmentioning
confidence: 99%
“…Single dose intraoperative radiotherapy (IORT) has gained popularity in the United States since the mid-2000s (1), with low complication and in-breast recurrence rates reported in the literature (1)(2)(3). Patients selected for IORT treatment are generally low risk individuals given their older age, smaller tumors, and high rates of estrogen receptor positivity (ER+) (1).…”
Section: Introductionmentioning
confidence: 99%
“…Single dose intraoperative radiotherapy (IORT) has gained popularity in the United States since the mid-2000s (1), with low complication and in-breast recurrence rates reported in the literature (1)(2)(3). Patients selected for IORT treatment are generally low risk individuals given their older age, smaller tumors, and high rates of estrogen receptor positivity (ER+) (1). The updated American Society for Radiation Oncology (ASTRO) consensus statement on partial breast irradiation delineates specific suitable characteristics (including 50 years of age or older with <2.5 cm screen detected invasive tumors of low or intermediate grade) for patients to be considered for low energy x-ray IORT treatment (3).…”
Section: Introductionmentioning
confidence: 99%